Cucumber (Cucumis sativus L.) relationship analysis using RAPD-PCR and isozyme methods - NUR INDAH JULISANIAH; LILIEK SULISTYOWATI; ARIFIN NOOR SUGIHARTO (Biodiversitas Journal of Biological Diversity, 2008)
RAPD-PCR method and isozyme analysis were used to obtain information of genetic relationship among cucumber varieties. Such information is urgently utilized to support plant breeding program of cucumber. Research was done at the Biotechnology Laboratory of Plant Pest and Diseases, Faculty of Agriculture of Brawijaya University, Malang and Molecular Biology Laboratory, Faculty of Matemathic and Natural Sciences of Brawijaya University, Malang. DNA isolation was done using CTAB method by additional NaCl modification. Sixteen primers from operon were employed to amplify DNA genome by RAPD-PCR. Two enzymes, Esterase and AAT were chosen for isozyme analysis. Clad 97 Program was used for analyzing the data and results in data grouping based on proximity value. Cluster analysis based on isozyme data indicated that there was an adequate lower genetic variation in cucumber, where seven of nine tested varieties showed proximity value of 1.00. Eleven of sixteen primers in RAPD-PCR analysis produced DNA bands. Relativity analysis by using RAPD-PCR method showed high enough of genetic variation. Relativity analysis by using both methods showed that variety 07 was the furthermost. The proximity value between varieties 01 and 02 was 0.916667, these varieties have the higest proximity value among allvarieties.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Cucumis sativus L., RAPD-PCR, isozyme.